2019
DOI: 10.3171/2019.2.spine18947
|View full text |Cite
|
Sign up to set email alerts
|

Use of incisional vacuum-assisted closure in the prevention of postoperative infection in high-risk patients who underwent spine surgery: a proof-of-concept study

Abstract: OBJECTIVEThis proof-of-concept study was conducted to determine whether negative-pressure wound therapy, through the use of incisional vacuum-assisted closure (VAC), is associated with a reduction in surgical site infections (SSIs) when compared to standard wound dressings in patients undergoing open posterior spinal fusion who have a high risk of infection.METHODSA total of 64 patients were examined; 21 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 17 publications
1
33
0
1
Order By: Relevance
“…Application of ciNPT has been reported to help create a closed environment over the incision, hold the wound edges together, reduce oedema, promote perfusion, and remove exudate via the application of constant negative pressure. Use of ciNPT has shown positive postoperative outcomes in patient populations with closed incisions resulting from groin wounds in vascular surgery, sternal reconstructive surgery, spine surgery, hip arthroplasty, and laparotomy . In this pilot study of 10 DIEP flap breast reconstruction patients, we compared outcomes of patients treated with ciNPT vs standard occlusive dressings.…”
Section: Discussionmentioning
confidence: 99%
“…Application of ciNPT has been reported to help create a closed environment over the incision, hold the wound edges together, reduce oedema, promote perfusion, and remove exudate via the application of constant negative pressure. Use of ciNPT has shown positive postoperative outcomes in patient populations with closed incisions resulting from groin wounds in vascular surgery, sternal reconstructive surgery, spine surgery, hip arthroplasty, and laparotomy . In this pilot study of 10 DIEP flap breast reconstruction patients, we compared outcomes of patients treated with ciNPT vs standard occlusive dressings.…”
Section: Discussionmentioning
confidence: 99%
“…22 Dyck et al have shown that the use of NPWT in the prevention of postoperative infection in high-risk patients who underwent spine surgery resulted in 50% reduction in surgical site infections. 23 In addition, others have shown not only a significant reduction in the incidence of postoperative wound infection but also wound dehiscence. 24 Following reconstruction, the patient receives q2H turns and lateral positioning during recovery so that pressure is avoided on the closure.…”
Section: Postoperative Considerationsmentioning
confidence: 99%
“…The use of NPWT in spine surgery has traditionally been in the treatment of post‐operative wound complications, including SSI 12,13 . More recently, it has been suggested that the use of ciNPT may reduce the incidence of SSI following spinal fusion procedures 14,15 . However, its potential applications in spinal surgery needs further clarification.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 More recently, it has been suggested that the use of ciNPT may reduce the incidence of SSI following spinal fusion procedures. 14,15 However, its potential applications in spinal surgery needs further clarification.…”
mentioning
confidence: 99%